Implementasi Kebijakan Bantuan Langsung Tunai (BLT) Dana Desa Bagi Masyarakat Terdampak Covid-19 (Studi pada Desa Pendarungan Kecamatan Kabat) - Zaki AL Mubarok; Slamet (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to find out how the implementation of the Village Fund Cash Direct Assistance (BLT) policy for communities affected by COVID-19 in Pendarungan Village, Kabat District and to find out what factors affect the implementation of the Village Fund Cash Direct Assistance (BLT) policy for communities affected by COVID-19. 19 in Pendarungan Village, Kabat District. The research approach used is a qualitative approach, namely a research procedure that allows researchers to study certain issues in depth and detail, because data collection is not limited to certain categories. Qualitative research is an inquiry process for understanding based on methodological inquiry traditions that clearly explore social and human problems. The data collection techniques that researchers use are observation, interview and documentation techniques. Meanwhile, the steps in data analysis in this research are data reduction, data display and conclusion drawing/verification. The results of the study show that in general the implementation of the BLT Dana Desa policy in general can be said to be going well in which the beneficiaries of the assistance have received BLT Dana Desa. Meanwhile, the factors that influence the implementation of the Village Fund Cash Direct Assistance (BLT) policy for communities affected by COVID-19 in Pendarungan Village, Kabat District, include; The village apparatus is minimal and must be faced with the many Covid-19 prevention programs that come to the village from the government and from the regional government. Compilation and determination of data on target communities who are entitled and eligible to receive social assistance, which empirically still finds errors. The mechanism in the process of implementing the Village Fund BLT policy.